Structural integrity assessment of sea water filtration overhead water tank and remedial measures – A case study - Prabakar, J.; Neelamegam, M.; Selvaraj, R.; Elangovan, R. (Journal of Structural Engineering, 2025)
A sea Water Filtration Overhead Tank was constructed in a coastal environment for the purpose of operating power plants during 1980. The overhead water tank consists of RCC columns, brace beams and storage reservoir at top. Due to the aging and also the pollutants from the atmosphere, the structural components, such as, columns, brace beams and reservoir slab have undergone corrosion damage by spalling of cover concrete and exposure of steel. The tank was investigated to assess the extent of damage and the cause of deterioration. The investigations included visual inspection, non destructive and partially destructive test, laboratory test and chemical analysis of the powder samples collected from the structure. Electrochemical parameters such as half cell potential and concrete resistivity were also measured. The test results indicated that the structural members were affected due to chloride ingress into the concrete which causes rebar corrosion. This paper describes the details of investigations carried out, evaluation of test rest results and recommendations for repair and strengthening of the structures to restore the operation.